AN ANALYSIS OF THE POSTAL MARKET CONCERNING 24/7 COURIER SERVICE AVAILABILITY (Perner's Contacts, 2020)
In this paper, we analyzed the readiness and needs of the postal market for the concept of express delivery service with improved time availability, which together with the existing services includes 24/7 customer service. On the territory of the city of Belgrade, a survey was conducted on the attitudes and needs for the existing services of express shipments, as well as for the proposed new service, in order to obtain appropriate indicators. The research involved creating an appropriate questionnaire and collecting the opinions of respondents, which consisted of individuals and legal entities. The collected data were statistically analyzed, and the most significant results were presented in the paper.
Keywords: expresní doručovací služba; zásilky; poštovní společnost; nová služba; časová dostupnost